2020
DOI: 10.13106/jafeb.2020.vol7.no10.909
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Life-Long Learning: An Empirical Study of Young People in Vietnam

Abstract: This study, not only investigates the important role of lifelong learning in shaping young people's knowledge and in maximizing their potential, but also aims to shed light on the influencing factors of lifelong learning of young people in Vietnam. The author applied STATA and SPSS to analyze quantitative data collected from questionnaires with 332 respondents aged between 19 years old and 24 years old. Based on a holistic review of literature, this study concludes that four driver factors affect young people'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, Vietnam could make a lesson to adapt it. The finding of Nguyen, Luu, & Ho (2020) also affirmed that the more staff are motivated, the more they can participate in LLL. Business employers based in Vietnam should develop working and incentive policies to motivate employees in their competitive careers by offering extra learning programs.…”
Section: Findings and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, Vietnam could make a lesson to adapt it. The finding of Nguyen, Luu, & Ho (2020) also affirmed that the more staff are motivated, the more they can participate in LLL. Business employers based in Vietnam should develop working and incentive policies to motivate employees in their competitive careers by offering extra learning programs.…”
Section: Findings and Discussionmentioning
confidence: 75%
“…The shortage of systematic and legal frameworks is the focus. Nguyen, Luu, & Ho (2020) examined the potential factors affecting LLL among 332 Vietnamese college students at economic universities aged 19 to 24. The results indicated that organizational culture and human resource development are primary elements.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Companies with greater employee involvement in decision-making, teamwork and innovative incentive systems need to train their employees in general skills for implementing those workplace practices successfully. Sharing of the work experience, the learning-oriented culture, the existence of staff responsible for training and the quality of HR management stimulates LLL (Nguyen et al , 2020; Mishra and Smith, 2015). The abovementioned research is related to H2 .…”
Section: Factors Affecting Firm’s Investments In Continuing Vocationa...mentioning
confidence: 99%
“…a focus on human resource management and development (Hayton et al , 1996; Smith et al , 2009; Mishra and Smith, 2015; Bishop, 2020; Nguyen et al , 2020).…”
Section: Factors Affecting Firm’s Investments In Continuing Vocationa...mentioning
confidence: 99%
See 1 more Smart Citation